Impact Des Réformes Sur La Compétitivité De La Production De Riz En Côte d’Ivoire Et Analyse De Sensibilité - Achy Landry (European Scientific Journal, ESJ, 2016)
The rice landscape since independence from the Ivory Coast to the present, is characterized by a series of government policies for the sector. The latest is the Revised National Strategy for Development of the rice sector (NRDS) 2012 - 2020. The central objective of this study is to analyze the impact on the competitiveness of producers, strategic guidelines defined by the NRDS. Our results indicate that it will generally have a positive effect on the competitiveness of production systems. But we find her, the existence of unfavorable conditions for the cultivation of upland rice system. Furthermore, a sensitivity analysis completing the foregoing analysis is performed. The results of this simulation show that: i) the increase in yield was identified as the only factor able to improve both financial profitability, external competitiveness (comparative advantage), reducing at the same time support producers; ii) the competitiveness of local rice increased with the overvaluation of the CFA. All these previous analyzes using the Policy Analysis Matrix (MAP) as an analytical model.